1932
DOI: 10.1007/bf01890391
|View full text |Cite
|
Sign up to set email alerts
|

Über die experimentelle Erzeugung siderofibröser Milzveränderungen

Abstract: In den letzten Jahren wurden mehrfaeh eigenartige, durch hohen Eisengehslt ausgezeiehnete Gebilde besehrieben, die in der dureh versehiedenartige krankhafte Vorg~nge vergnderten Milz (selten ~ in anderen Organen) gefunden wurden und fiber deren Entstehung und Wesen lebhafter Streit entbrannte.Es handelt sich um verschieden grol~e Herde, yon denen einige auf der Schnittfl~che der Milz, als umschriebene, tabakfarbene Flecke schon mit freiem Auge erkennbar sind. Das Mikroskop deckt an ihnen tiefgreifende Veri~nde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1936
1936
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The same author also showed in an animal model that injecting bilirubin compounds reproduced splenic granulomatosis [22]. Later on, other authors confirmed this data by similar experiments showing that GGBs represent an inducible lesion [23,24]. The amorphous inclusions were shown to be positive for lipofuschin material, (compatible with broken cell membrane) [25].…”
Section: Discussionmentioning
confidence: 51%
“…The same author also showed in an animal model that injecting bilirubin compounds reproduced splenic granulomatosis [22]. Later on, other authors confirmed this data by similar experiments showing that GGBs represent an inducible lesion [23,24]. The amorphous inclusions were shown to be positive for lipofuschin material, (compatible with broken cell membrane) [25].…”
Section: Discussionmentioning
confidence: 51%